La teología de Nicolás de Cusa : un desafío para la elaboración de una teología natural - Rego, Francisco (Sapientia, 2007)
Nicholas of Cusa has the aim to solve the impasse that the theological field implies the rejection of metaphysical knowledge proposed by nominalism. His peculiar interpretation of God’s nature and of his way of knowing it that which allowed to him to found a new theology ordered to overcome the limitations of a knowledge that, according to him, was able to know the finite order only. In this sense Nicholas suggests to replace the way of rational knowledge by means of another of a pure intuitive character. The essential trait of this intuitive knowledge is to know not knowing, i.e., the way of the learned ignorance (docta ignorantia). Trough this way man can reach certain knowledge of mystical nature which would be comparable with that knowledge of the eternal bliss only. Here the author tries to determine whether, on the basis offered by Nicholas, is it possible to hold a natural theology and, furthermore, a mystical one.